Current evidence on the effect of highly effective CFTR modulation on interleukin-8 in cystic fibrosis. Issue 1 (2nd January 2022) - Williamson, Michael; Casey, Michelle; Gabillard-Lefort, Claudie; Alharbi, Aram; Teo, Yu Qing Jolene; McElvaney, Noel G; Reeves, Emer P.
ABSTRACT: Introduction: Cystic fibrosis (CF) is a genetically inherited disease, with mortality and morbidity associated with respiratory disease. The inflammatory response in CF is characterized by excessive neutrophil influx to the airways, mainly due to the increased local production and retention of interleukin-8 (IL-8), a potent neutrophil chemoattractant. Areas covered: We discuss how the chemokine IL-8 dominates the inflammatory profile of the airways in CF lung disease. Cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies are designed to correct the malfunctioning protein resulting from specific CFTR mutations. This review covers current evidence on the impact of CFTR impairment on levels of IL-8 and outlines the influence of effective CFTR modulation on inflammation in CF with a focus on cytokine production. Review of the literature was carried out using the PUBMED database, Google Scholar, and The Cochrane Library databases, using several appropriate generic terms. Expert opinion: Therapeutic interventions specifically targeting the defective CFTR protein have improved the outlook for CF. Accumulating studies on the effect of highly effective CFTR modulation on inflammation indicate an impact on IL-8 levels. Further studies are required to increase our knowledge of early onset innate inflammatory dysregulation and on anti-inflammatory mechanisms of CFTR modulators.